Demographic and Labor Potential as the Factors of Agroecotourism Development in Belarus (on the Example of Brest and Grodno Regions) - Liudmila Fakeyeva; Aliaksei Shadrakou (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2016)
In the following article demographic development is analysed as a factor of agroecotourism development in Belarus with special emphasis on Brest and Grodno Regions as areas with the highest potential for rural tourism progress and expansion. The potential role for rural tourism development of demographic potential, labor resources and settlement system is revealed. The demographic development of Belarusian rural areas is presented for the period of 1970–2013. The article aims to work out the typology of districts in accordance with peculiarities of demographic development during this period. The article also aims to trace the main factors of demographic spatial inequality in rural areas in Belarus.